Nowożytne próby rekonstrukcji ustawy XII Tablic - Zabłocka, Maria (Prawo Kanoniczne, 1994)
Legal humanism brought special interests in the Roman law sources that are earlier than the Justinian’s codification. It was focused on the Twelve Tables statute - the oldest legal source. Aymarus Rivallius and Alexander ab Alexandro combined its elements, but did not make an effort to reconstruct the composition. Johann Oldendorp only formally related to the statute. In the matter of fact, the order of his reconstruction was based on the Cicero’s classification of branches of law into ius sacrum, ius publicum and ius privatum, that was presented in his De legibus. Earlier, the very same scheme was used in the reconstruction of Hotomanus and in that of Corpus Iuris Civilis, Lugduni 1600. The latter reconstruction made the Twelve Tables better known to the broad public and enhanced reaserches on the oldest legal source of Roman law.